Compressive strength of collar plate reinforced SHS T-joints: Effect of geometrical parameters and chord stress ratio. (November 2020) - Chang, Hongfei; Zuo, Wenkang; Yang, Jianchao; Song, Xinyi; Huang, Yuner
Abstract: The collar plate (CP) is applicable for the reinforcement of both new designed and in-service joints, yet the design approach for the reinforcement requires further investigation. The current paper investigates the effect of various geometrical parameters as well as chord stress ratios on the compressive capacity of the collar plate reinforced (CPR) square hollow section (SHS) T-joints. The finite element (FE) models of the CPR SHS T-joints are built and validated using experimental data. Extensive parametric studies are carried out to evaluate the influence of parameters such as the brace to chord width ratio, the width/length and thickness of the CP, as well as the chord stress ratio. The brace to chord width ratio and the CP thickness are identified as the key parameters, and three typical failure modes are observed. Finally, bearing mechanism of CPR T-joints is discussed and design equations are proposed based on the failure modes. The failure-mode-based equations agree well with both parametric data and orthogonal analysis results, which provides reference for the practicing engineers. Graphical abstract: Unlabelled Image Highlights: Effect of geometrical parameters and chord stress on the compressive strength of CPR SHS T-joint is investigated; Typical failure modes of the CPR SHS T-joints under compressive load are identified; Design equations are established to determine the compressive strength of CPR SHS T-joints.